Soft-Switching Power Electronics Technology for Electric Vehicles: A Technology Review - Pahlevani, Majid; Jain, Praveen K. (IEEE journal of emerging and selected topics in industrial electronics (Print), 2020)
Power electronic converters for electric vehicles (EVs) have been the subject of great interest over the last several decades. This article presents a thorough review of different EV power electronic converters on which the authors have worked for more than one decade. The readers will find this review interesting to design current products and to devise/invent new converters for emerging applications in EV.